THE EFFECT OF INQUIRY-BASED LEARNING STRATEGY ON THE STUDENTS' ACHIEVEMENTS AND ATTITUDES TOWARDS SCIENCE AND TECHNOLOGY - Gonca KEÇECİ; Pelin YILDIRIM (International Journal of Eurasia Social Sciences, 2017)
This study was carried out in order to determine the effect of inquiry-based learning strategy on the 7th grade students' achievements and attitudes towards science and technology. In the study, Grade 7, "Force and Energy" unit, "Pressure" subject was taught by applying guided inquiry based learning activities. The study was carried out in the 2015-2016 academic year with a total of 31 seventh grade students, 13 girls and 16 boys. In this study, quasi-experimental pre-test-post-test control group design was used. The data of the study were collected using the Pressure Achievement Test (PAT) and the Science and Technology Attitude Scale (STAS). The pre-test and post-test scores obtained from the PAT and the STAS were analyzed using the t-test. As a result of the implemented practices, it has been found that there is a significant increase in the success levels of the students, t(30)=-8.197, p=.00<.01. When the data obtained from the Science and Technology Attitude Scale were analyzed, it was seen that there was a significant increase in students' attitudes towards science and technology, t(30)=-10.040, p=00<.01. The continuity of the earnings can be achieved by applying the inquiry based learning to other science subjects.